Extrinsic Factors Regulating Dendritic Patterning - Lin, Tzu-Yang; Chen, Pei-Ju; Yu, Hung-Hsiang; Hsu, Chao-Ping; Lee, Chi-Hon (Frontiers in Cellular Neuroscience, 2021)
Stereotypic dendrite arborizations are key morphological features of neuronal identity, as the size, shape and location of dendritic trees determine the synaptic input fields and how information is integrated within developed neural circuits. In this review, we focus on the actions of extrinsic intercellular communication factors and their effects on intrinsic developmental processes that lead to dendrite patterning. Surrounding neurons or supporting cells express adhesion receptors and secreted proteins that respectively, act via direct contact or over short distances to shape, size, and localize dendrites during specific developmental stages. The different ligand-receptor interactions and downstream signaling events appear to direct dendrite morphogenesis by converging on two categorical mechanisms: local cytoskeletal and adhesion modulation and global transcriptional regulation of key dendritic growth components, such as lipid synthesis enzymes. Recent work has begun to uncover how the coordinated signaling of multiple extrinsic factors promotes complexity in dendritic trees and ensures robust dendritic patterning.